2022
DOI: 10.3389/fimmu.2022.966417
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induced gut dysbiosis contributes to disease severity in an animal model of multiple sclerosis

Abstract: BackgroundMultiple sclerosis (MS) is an inflammatory and demyelinating disease of the CNS. The etiology of MS is complex, and results from the interaction of multiple environmental and genetic factors. Although human leukocyte antigen-HLA alleles such as HLA-DR2 and –DR3 are considered the strongest genetic factors, the environmental factors responsible for disease predisposition are not well understood. Recently, diet and gut microbiota have emerged as an important environmental factors linked to the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…This is further corroborated by the observed shifts in the microbiome in a variety of disease states and chronic in ammatory conditions [6,7]. For instance, both gut and oral dysbiosis have been linked to obesity, as evidenced in laboratory investigations and patient cohorts [8,9,10]. We and others have previously reported that different ART regimens could have distinct modulating effects on the gut microbiome due to the anti-microbial properties of speci c antivirals [5,11,12].…”
Section: Introductionmentioning
confidence: 71%
“…This is further corroborated by the observed shifts in the microbiome in a variety of disease states and chronic in ammatory conditions [6,7]. For instance, both gut and oral dysbiosis have been linked to obesity, as evidenced in laboratory investigations and patient cohorts [8,9,10]. We and others have previously reported that different ART regimens could have distinct modulating effects on the gut microbiome due to the anti-microbial properties of speci c antivirals [5,11,12].…”
Section: Introductionmentioning
confidence: 71%
“…These OTUs were significantly correlated with different clinical parameters including HbA1c, the lipid profile and hypertension. Microbes considered to be associated with dysbiosis such as Bilophila [ 33 ], Sutterella [ 34 ] and Desulfovibrionaceae [ 35 ] were correlated with a worse clinical tableau in the case of T2D patients. Conversely, the presence of F. prausnitzii in the T2D microbiome was associated with improved metabolic parameters such as LDL and HDL.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these factors can cause dysbiosis (an imbalance of the composition, metabolism or distribution of the microbiome associated with an unhealthy outcome) and have been investigated for their role in a wide range of human diseases (274). These include obesity, diabetes, gestational diabetes, metabolic syndrome, cardiovascular disease, inflammatory bowel disease, multiple sclerosis, dementia, PCOS, and many others (275,276). Lifestyle-related disturbance to the balanced microbial ecosystem contributes to a variety of diseases, depending on the level of exposure, length of exposure, combination of exposures, and individual disease susceptibility (274).…”
Section: Central Role Of the Microbiome In The Pathogenesis Of Pcosmentioning
confidence: 99%